ROLE-PLAYING EXERCISES AS A METHOD OF TEACHING COMMUNICATIVE SKILLS - Shcherbina, V.V. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2014)
The article is devoted to the analysis of role-playing activities in their combination with the other English language teaching techniques at all the stages of an English lesson. The set of role-playing activities efficient for the development of communicative skills has been offered.